Environmental PM2.5, Physical Activity Levels, and Aerobic Capacity, of Smokers and Non-Smokers - Shukla, Mayank; Bansal, Sakshi (Journal of Community Medicine and Health Solutions, 2023)
Aerobic capacity of young men (19 years - 24 years) is high, but can be influenced by many factors like physical activity, smoking, and air pollution with environmental PM2.5. Objectives: (a) - to estimate the aerobic capacity in young men (smokers and non-smokers) living in areas with higher PM2.5 using Queen’s College Step Test (QCT). (b) - to find whether aerobic capacity is associated with the International Physical Activity Questionnaire (IPAQ)’ three classes, for smokers and non-smokers. Methods: In a cross-sectional study using criteria-based sampling a total of n = 60 smokers & non-smokers were included from the Delhi NCR region. IPAQ, Peak Expiratory Flow Rate (PEFR), Heart Rate, Systolic Blood Pressure, Diastolic Blood Pressure, and PM2.5 and PM10 levels were recorded. A comparison of smokers and non-smokers was performed using z test. Smokers and non-smokers were divided into three classes using physical activity levels and compared for aerobic capacity. The correlation of aerobic capacity with variables was seen using Pearson’s correlation coefficient. Multiple R was checked to study the model of cause and effect for aerobic capacity. Results: Significant difference is seen between smokers and non-smokers in the aerobic capacity (Mean ± SD smokers - 65.22 ± 8.73 ml/kg/min; Mean ± SD non-smokers 60.04 ± 7.7 ml/kg/min p value = 0.00). For non-smokers, a low level of physical activity shows a strong correlation with aerobic capacity (r = 0.78; p = < 0.05). No correlation of aerobic capacity is seen with physical activity levels among smokers. Aerobic capacity shows a significant negative and moderate correlation with PM2.5 (r = -3.1; p = 0.016). The multiple R coefficient value for the model of cause and effect is 6.99 with a p - value of 0.0449 for this. Conclusion: Smoking affects aerobic capacity significantly for young men. High and moderate levels of outdoor physical activity do not increase aerobic capacity in areas with high PM2.5, whereas low levels show a positive correlation among non-smokers only.